Selection of Amino Acid Chirality Induced by Cyclic Dipeptide Synthesis in Plausible Prebiotic Conditions - Guo, Yeting; Zhang, Yumeng; Ying, Jianxi; Liu, Yan; Zhang, Gaiyun; Zhao, Yufen (Frontiers in Astronomy and Space Sciences, 2022)
The biological system uses L-amino acids (L-AAs) to construct peptides. The selection of AA chirality in the prebiotic Earth still remains a mystery. Here we report the intrinsic mechanism of AA chiral selection in the formation of prebiotic proline-containing cyclic dipeptide (DKPs). The DKPs were synthesized by equal amounts of L-AA and D-AA with L-Pro that exhibited a clear preference for D-AA as opposed to L-AA. And surprisingly, the L-AA was preferred over D-AA in the mirror-image system with D-Pro. These results indicate that prebiotic DKPs synthesis has a certain selectivity for AA chirality preceded the biological enzymatic catalysis.